Spanish Photography Yearbooks between the Autarchy and the Transition A Documentary Analysis (1958-1980) - Sánchez Vigil, Juan Manuel (Revista General de Información y Documentación, 2016)
The first yearbook on Spanish artistic photography was published in 1924 and following the Civil War of 1936-1939, Madrid’s Real Sociedad Fotográfica, through its Sombras magazine, published two others in 1946 and 1948. There would not be another publication until 1958, when the Agrupación Fotográfica Almeriense put out the third yearbook, during a period of economic recovery following the country’s admission to the U.N. at the end of 1955. However, it was not until 1972 when Spanish photography resumed the publication of annual summaries of the authors and their works. From then on until 1980, nine yearbooks were published by two institutions: The Consorcio del Libro Técnico (Cotec) and the Editorial Everest publishing company. The object of this study is to analyze the contents of these yearbooks in order to determine and furnish new data on the history of Spanish photography: authors, works, publications, national and international relations and the purpose of their publications as a means for supporting photography.
Keywords: Afal; photography yearbook; consorcio del libro técnico; Cotec; Cotecflash; Everfoto; photography; history of spanish photography; Spafoto